Biological Pacemakers â A Review - Gunasekaran, Velvizhi; Selvaraj, Raja (International Journal of Cardiovascular Practice, 2018)
Slow heart rates, due to sinus node disease or atrioventricular conduction block, are a significant problem for many patients. Currently, these patients are treated with electronic pacemakers, which provide effective therapy, but are also associated with many problems. Use of biological pacemakers is an attractive solution to these problems. Approaches for the creation of such pacemakers include either the injection of cells that have pacemaker activity (cell-based approach) or modification of cells in the heart to induce pacemaker activity by delivering genes (gene-based approach). This article reviews the progress in the development of biological pacemakers.